Genome signature comparisons among prokaryote, plasmid, and mitochondrial DNA - Campbell, Allan (The National Academy of Sciences, 1999)
Our basic observation is that each genome has a characteristic “signature” defined as the ratios between the observed dinucleotide frequencies and the frequencies expected if neighbors were chosen at random (dinucleotide relative abundances). The remarkable fact is that the signature is relatively constant throughout the genome; i.e., the patterns and levels of dinucleotide relative abundances of every 50-kb segment of the genome are about the same. Comparison of the signatures of different genomes provides a measure of similarity which has the advantage that it looks at all the DNA of an organism and does not depend on the ability to align homologous sequences of specific genes. Genome signature comparisons show that plasmids, both specialized and broad-range, and their hosts have substantially compatible (similar) genome signatures. Mammalian mitochondrial (Mt) genomes are very similar, and animal and fungal Mt are generally moderately similar, but they diverge significantly from plant and protist Mt sets. Moreover, Mt genome signature differences between species parallel the corresponding nuclear genome signature differences, despite large differences between Mt and host nuclear signatures. In signature terms, we find that the archaea are not a coherent clade. For example, Sulfolobus and Halobacterium are extremely divergent. There is no consistent pattern of signature differences among thermophiles. More generally, grouping prokaryotes by environmental criteria (e.g., habitat propensities, osmolarity tolerance, chemical conditions) reveals no correlations in genome signature.